STARS Adjunct Trial: Evidence for the Effectiveness of a Digital Therapeutic as Adjunct to Treatment With Medication in Pediatric ADHD. (April 2023) - Maple, Amanda; Palko, Lisa; Cañadas, Elena; Jina, Anil
Abstract: Background: Treatment of attention deficit hyperactivity disorder (ADHD) includes pharmacological and non-pharmacological interventions, both of which have demonstrated short-term efficacy. While efficacious, there are limitations to both modalities of treatment. Due partly to these limitations, there has been considerable interest in additional approaches to augmenting ADHD management. Digital therapeutics may offer improved access, minimal side effects, and low potential for abuse, while providing targeted treatment options for improving cognitive functions such as attention. AKL-T01 (EndeavorRx®) is the first and only FDA-cleared nonpharmacological prescription digital therapeutic delivered through a video game interface for the treatment of ADHD. Objective: The objective is to summarize the data from a clinical trial in support of FDA clearance using AKL-T01 adjunctively in children currently taking stimulant medication for ADHD. Methods: The STARS-Adjunct Trial was a multicenter, 12-week, open-label study of AKL-T01 in 206 children aged 8 to 14 years with a confirmed diagnosis of primarily inattentive or combined-type ADHD. The study included two cohorts: (1) subjects currently treated with ADHD medication (n=130) and (2) subjects not on any ADHD medication (n=76). Subjects had an ADHD Impairment Rating Scale (IRS) score ≥3 at baseline, and both cohorts used AKL-T01 for approximately 25 minutes per day, 5 days per week, over two 4-week treatment periods separated by a 4-week treatment pause. Results: AKL-T01 significantly improved (lowered) ADHD-related impairment as measured with the IRS (clinician rated) after the first 4-week treatment in both cohorts (P< 0.001). Results show that effects persist during a 4-week treatment pause and further improve with a second 4-week treatment period. A majority of parents and children indicated a perceived improvement in ability to pay attention after the trial. Most common device-related adverse events were decreased frustration tolerance, headache, and irritability which ranged from mild to moderate. No serious adverse events were reported. Conclusions: This study adds to and extends the clinical evidence base for AKL-T01, a video game-based treatment for improving attentional functioning in 8–12-year-old children with ADHD. Continued evaluation of the effects of AKL-T01 on other important aspects of functioning, like academic and social functioning, health utilization, and health outcomes, would continue to add to the evidence base that the effects observed in this and previous studies have substantial clinical and functional impact. Funding: Akili Interactive